The impact of blockchain technology on tourism intermediation - Melkić, Sara (Array, 2020)
Contemporary tourism has undergone many changes in the last decade, mainly due to expansion of the new technology. The use of new technology has had more positive than negative impacts on tourism intermediation, but none of them triggered a radical change. Blockchain technology has been one of the most discussed topics especially after 2016 due to its all opportunities, but also threats. Even though it is still somewhat unfamiliar, it is a form of technology which has a great potential to cause a revolution in traditional business activities, as it is predicted by futurists. For now, this phenomenon has only been recognized by bigger tourism intermediaries, technology-oriented companies. Such fast changes require even faster adaptations of all tourism intermediaries and this is challenging because most of stakeholders are not familiar with the use and the impact of blockchain. Therefore, in this paper the authors will try to provide answers by presenting a SWOT analysis of blockchain technology implications on activities undertaken by all participants in tourism intermediation. It implies to conclusion that everyone will face various challenges in its implementation which have to be considered seriously. The use and the general understanding of blockchain technology is still in an initial stage, so it is crucial that tourism research takes a proactive role in the exploration of this field of study. Furthermore, as trends are dynamic and evolve rapidly, the topic becomes particularly challenging for scientists in bridging practice into theory. Therefore, this theory-based paper on an overall assumption contributes to a better understanding of this phenomenon and raises the awareness for further research.